Severe glomerular disease in juvenile grey snapper Lutjanus griseus L. in the Gulf of Mexico caused by the myxozoan Sphaerospora motemarini n. sp - Holzer, Astrid S; Pecková, Hanka; Patra, Sneha; Brennan, Nathan P; Yanes-Roca, Carlos; Main, Kevan L (International journal for parasitology. Parasites and wildlife, 2013)
In the eastern Gulf of Mexico, off the coast of Florida, grey snapper, Lutjanus griseus was found to be infected with the myxozoan parasite Sphaerospora motemarini n. sp., with high prevalence (83%) and intensity of infection occuring in age-0 fish, and with parasite levels decreasing with age (age-1 snapper 40%; age-2 snapper 0%). The morphological, molecular and phylogenetic characterisation of the myxozoan showed that it is a member of the typically marine, polysporoplasmid Sphaerospora spp. which form a subclade within the Sphaerospora sensu stricto clade of myxozoans, which is characterised by large expansion segments in their SSU rDNA sequences. Presporogonic stages of S. motemarini n. sp. were detected in the blood, using PCR. Pseudoplasmodia and spores were found to develop in the renal corpuscles of the host, causing their massive expansion. Macroscopic and histopathological changes were observed in age-0 fish and show that S. motemarini n. sp. causes severe glomerulonephritis in L. griseus leading to a compromised host condition, which makes it more susceptible to stress (catch-and-release, predators, water quality) and can result in mortalities. These results are discussed in relation to the exploitation of grey snapper populations by commercial and recreational fisheries and with the observed increased mortalities with temperature along the coast of Florida. In the future, we would like to determine prevalence and intensity of infection with S. motemarini n. sp. in juvenile L. griseus in different areas of the Gulf of Mexico in order to be able to estimate the temperature dependence of S. motemarini n. sp. proliferation and to be able to predict its distribution and severity during climatic changes in the Gulf.
Keywords: Juvenile pathology; Mangrove snapper; Glomerulonephritis; Fisheries; Myxozoa; Mortality